The Effect Of Growth Opportunity and Profitability On Company Value On The Stock Exchange Indonesia (BEI) Period 2018-2022 - Vedi Oktavia Fitry Ani; Yohanes Indrayono; Hendro Sasongko (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Based on data from the United Nations Industrial Development Organization (UNIDO), Indonesia is the country with the most influential manufacturing industry value in the world, but from the other side, based on data, the growth of the manufacturing industry in Indonesia experienced a significant decline in 2020, this is due to the condition of the closure of the capital structure and the impact The Covid-19 pandemic has weakened the value of investment in manufacturing industry companies, which has an impact on growth opportunities. Apart from that, the profitability of manufacturing industry companies has weakened, potentially leading to a decline in company value. Therefore, the aim of this research is to understand the factors that influence the value of manufacturing industry companies. Through capital structure as an intervention, the data used in this research is secondary data used in the form of annual financial report data of manufacturing companies for the 2018-2022 period obtained from the Indonesia Stock Exchange (BEI) website, namely www.idx.co.id with the sample size using Purposive sampling is based on criteria so that from 236 companies we get a sample of 115 companies. The analysis method used is descriptive statistical analysis, panel data regression analysis, and Sobel test using e-views version 10. Analysis of manufacturing company data on the 2018-2022 BEI shows that the effect is significant. direct negative impact on capital structure.